On The Local Edge Antimagic Coloring of Corona Product of Path and Cycle - Aisyah, Siti; Alfarisi, Ridho; Prihandini, Rafiantika M.; Kristiana, Arika Indah; Christyanti, Ratna Dwi (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2019)
Let be a nontrivial and connected graph of vertex set and edge set . A bijection is called a local edge antimagic labeling if for any two adjacent edges and , where for . Thus, the local edge antimagic labeling induces a proper edge coloring of G if each edge e assigned the color . The color of each an edge e = uv is assigned bywhich is defined by the sum of label both and vertices and . The local edge antimagic chromatic number, denoted by is the minimum number of colors taken over all colorings induced by local edge antimagic labeling of . In our paper, we present the local edge antimagic coloring of corona product of path and cycle, namely path corona cycle, cycle corona path, path corona path, cycle corona cycle.Keywords: Local antimagic; edge coloring; corona product; path; cycle.